FASE-FASE PENDIDIKAN ANAK DALAM KONTEKS HADITS - Mukhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the stages of children's education in the context of hadith. The research method used is a literature study with a qualitative approach. Data were collected from various relevant hadith sources and analyzed to identify the principles of children's education taught by the Prophet Muhammad SAW. The results of the study indicate that the hadith provides comprehensive guidance on children's education, from the infant phase to adolescence, emphasizing the importance of affection, discipline, and teaching moral values. These findings provide an important contribution to the development of an Islamic education curriculum based on the teachings of the hadith.